Big bang disruption : strategy in the age of devastating innovation - Downes, Larry, 1959-; Nunes, Paul, 1963- (2014)
"Free navigation apps on smartphones wreaked havoc for the makers of standalone GPS devices. Airbnb and other resource sharing services are undermining hotels. Uber, SideCar and Lyft are reinventing the heavily regulated taxi and limousine industry. These are just a few of hundreds of examples of Big Bang Disruptions-new products and services that enter the market better and cheaper than established products, seemingly overnight. Driven by falling prices for component parts, rapid experimentation with real customers, and the delivery platforms of the Internet and the cloud, they are different in kind from previous generations of innovations. Their frequency is only going to accelerate. Every industry is at risk. Big Bang Disruption presents a radical new framework for this phenomenon. Larry Downes and Paul F. Nunes offer critical insights and strategies companies are using not just to protect themselves but to create and appropriate disruptive innovations for themselves. The authors detail the four stages of big bang innovation and show leaders how to see disruptions headed their way-and take action before it's too late"--
Includes bibliographical references (pages 243-245) and index.
Keywords: BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / General; New business enterprises; Technological innovations; Strategic planning